1999
DOI: 10.1007/s005850050804
|View full text |Cite
|
Sign up to set email alerts
|

ULF wave occurrence statistics in a high-latitude HF Doppler sounder

Abstract: Ultra low frequency (ULF) wave activity in the high-latitude ionosphere has been observed by a high frequency (HF) Doppler sounder located at Tromsù, Norway (69.7°N, 19.2°E geographic coordinates). A statistical study of the occurrence of these waves has been undertaken from data collected between 1979 and 1984. The diurnal, seasonal, solar cycle and geomagnetic activity variations in occurrence have been investigated. The ®ndings demonstrate that the ability of the sounder to detect ULF wave signatures maximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The local time dependence of spectral power and polarization presented here is the result of the statistical analysis over the entire interval of data. A separate investigation (not shown here) conducted for the different seasons showed that the results of the present analysis are permanent features at SP, largely independent of season, although somewhat more prominent during equinoxes [e.g., Rao and Gupta , 1978; Wright et al , 1999].…”
Section: Data Analysis and Experimental Resultsmentioning
confidence: 59%
“…The local time dependence of spectral power and polarization presented here is the result of the statistical analysis over the entire interval of data. A separate investigation (not shown here) conducted for the different seasons showed that the results of the present analysis are permanent features at SP, largely independent of season, although somewhat more prominent during equinoxes [e.g., Rao and Gupta , 1978; Wright et al , 1999].…”
Section: Data Analysis and Experimental Resultsmentioning
confidence: 59%
“…Comparisons between ULF wave activity recorded by ground based magnetometers and associated variations in the frequency of HF waves reflected from the ionosphere have been reported by a number of researchers (Watermann, 1987;Menk, 1992;Wright et al, 1999). Most studies employ a "Doppler sounder" configuration consisting of a continuous wave (CW) transmitter/receiver system that monitors an ultra-stable frequency in the HF band.…”
Section: Introductionmentioning
confidence: 99%